PERAN PRODUSER DALAM PROSES PRODUKSI WEB SERIES PERDANA WAHANA HONDA - Nazilah, Silmi (Jurnal Visi Komunikasi, 2022)
Wahana Honda is one of the businesses engaged in the distribution of Honda motorcycles and the service of Honda motorcycles is one of the services of Wahana Honda. This research uses descriptive research method with a qualitative approach. The method used is a case study by conducting in-depth interviews with informants. The results of this study indicate that the role of producers in the Wahana Honda Prime web series process consists of 3 stages, in pre-production which of course it is related in making themes, story ideas, cinematographic processes in the production and editing of images. In the production process the producer is fully responsible for controlling, supervising, and coordinating to all the crew involved for the smooth running of their production, carrying out production in accordance with the script and shooting script made by the producer. In post production there are 2 editing processes, namely offline and online. The producer ensures and supervises the production work in accordance with the client's direction and deliver the results in accordance with the agreed time.